Comparing Resident, Proxy, and Staff Respondents for Nursing Home Residents' Preferences for Everyday Living. (January 2023) - Kunicki, Zachary J.; Madrigal, Caroline; Quach, Lien T.; Riester, Melissa R.; Jiang, Lan; Duprey, Matthew S.; Bozzay, Melanie; Zullo, Andrew R.; Singh, Mriganka; McGeary, John; Wu, Wen-Chih; Rudolph, James L.
To encourage person-centered care, the Centers for Medicare and Medicaid require nursing homes to measure resident preferences using the Preferences Assessment Tool (PAT). No known research has examined the implications of respondent type (i.e., resident, proxy, staff) on preference importance; therefore, the purpose of this study was to compare the importance of preferences depending on which respondent completed the PAT. Participants included 16, 111 Veterans discharged to community-based skilled nursing facilities after hospitalization for heart failure. A majority (95%) of residents completed the PAT compared to proxy (3%) and staff (2%). Proxy responders were both more and less likely to indicate individual preferences as important compared to residents. Staff members were consistently less likely to indicate all preferences as important compared to residents. Findings from this study emphasize the need for proxy and staff to find methods to better understand residents' preferences when residents are not able to participate in assessments.